2020
DOI: 10.3390/coatings10020114
|View full text |Cite
|
Sign up to set email alerts
|

Eudragit S100 Entrapped Liposome for Curcumin Delivery: Anti-Oxidative Effect in Caco-2 Cells

Abstract: Curcumin is a natural polyphenol with strong antioxidant activity. However, this molecule shows a very poor bioavailability, instability, and rapid metabolism in vivo. In this work curcumin was loaded in Eudragit-coated liposomes to create a gastroresistant carrier, able to protect its load from degradation and free it at the site of absorption in the colon region. Small unilamellar vesicles were prepared and coated with Eudragit by a pH-driven method. The physico-chemical properties of the prepared systems we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Indeed, recent studies underlined that the incorporation of phytocomplexes in ad hoc modified phospholipid vesicles, can improve their local efficacy in vivo 69 . Recently, De Leo et al 70 incorporated curcumin in eudragit-coated liposomes to create a gastro-resistant carrier, able to protect the payload and deliver it in the colon. Hasibi et al 71 formulated transfersomes containing Tween 80 or Span 60 and confirmed their ability to slowly release taxifolin at intestinal level without evaluating their stability at acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies underlined that the incorporation of phytocomplexes in ad hoc modified phospholipid vesicles, can improve their local efficacy in vivo 69 . Recently, De Leo et al 70 incorporated curcumin in eudragit-coated liposomes to create a gastro-resistant carrier, able to protect the payload and deliver it in the colon. Hasibi et al 71 formulated transfersomes containing Tween 80 or Span 60 and confirmed their ability to slowly release taxifolin at intestinal level without evaluating their stability at acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-loaded liposomes displayed the same antioxidant activity of free curcumin in ethanol, a negligible antioxidant activity when covered with the polymer, which reversed to the normal one after polymer removal. In a subsequent work [ 19 ], the uptake by Caco-2 cells of vesicles loaded with curcumin and coated with Eudragit S100 was assessed. At pH > 7.0, the Eudragit S-100 coating dissolves, releasing the nanometric liposomes and allowing them to enter Caco-2 cells.…”
Section: Polymer/liposome Assembly To Confer Stimuli-responsive Prmentioning
confidence: 99%
“…Numerous beneficial properties are recognized to this molecule, since many studies have confirmed its antioxidant, anti-inflammatory, antibacterial, and even anti-cancer properties. In order to increase CM water solubility, thus improving its stability and bioavailability, several strategies have been adopted, the main one being the inclusion in liposomes, micelles, solid lipid nanoparticles and in general in polymolecular aggregates of lipids, surfactants, and biopolymers, often in combination with each other [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous beneficial properties are recognized to this molecule, since many studies have confirmed its antioxidant, anti-inflammatory, antibacterial, and even anti-cancer properties. In order to increase CM water solubility, thus improving its stability and bioavailability, several strategies have been adopted, the main one being the inclusion in liposomes, micelles, solid lipid nanoparticles and in general in polymolecular aggregates of lipids, surfactants, and biopolymers, often in combination with each other [14][15][16]. In addition, because of its properties, CM has often been incorporated, functionalized, and conjugated to polymers as a dye, to improve the usability of CM in the field of drug delivery, or to obtain antibacterial, anticancer, and anti-inflammatory biocompatible materials [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%